Evaluación del control interno contable y su incidencia en el presupuesto Dirección Distrital 12D01 Baba Babahoyo Montalvo-educación año 2014 - Mendoza Villasnay, Verónica Mariuxi (2016)
This research was conducted in the province of Los Rios Babahoyo Canton, in the District of Education, located at 102 and General Mejia Barona The investigative phase lasted 120 days. Its general objective was to evaluate internal control and its impact on the district budget Canton Babahoyo, Los Rios province. 2014, and the specific objectives is to analyze and identify the internal control environment that exists in the District Direction 12D01 Baba - Babahoyo - Montalvo - education; Check the internal control activities implemented in the budget processes of the District Direction 12D01 Baba - Babahoyo - Montalvo - education; Prepare the report of the results of the evaluation of internal control of the District Direction 12D01 Baba - Babahoyo - Montalvo - education. For this research the analytical and inductive methods were used, and the technique of observation. The results of the investigation were made as follows: Once made a diagnosis is concluded that the internal control is carried out without properly, lack of organization in what refers to perform excellent control of activities not apply due process because there is lack of staff ESIGEF management system due to lack of training Keywords: internal control, budget, evaluate activities.